2002
DOI: 10.1002/ptr.784
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory property of the leaves of Gongronema latifolium

Abstract: An aqueous extract of the dried leaves of Gongronema latifolium was studied for its antiinflammatory activity. The extract significantly (p < 0.05) inhibited carrageenan-induced rat paw oedema, carrageen-induced leucocyte migration in rats and dye leakage induced by intraperitoneal injection of acetic acid in mice. These results demonstrate the antiinflammatory property of G. latifolium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 6 publications
(7 reference statements)
5
77
0
Order By: Relevance
“…This observation agrees with previous reports by Oshodi et al(2004) that aqueous extracts of G. latifolium extracts show no activity against S. aureus. Results obtained in this work complement previous report on the usefulness of G. latifolium (Ugochukwu and Babady, 2002;Farombi, 2003;Morebise et al, 2002). Although compounds responsible for the observed bioactivity are unknown at this point, preliminary works and other reports show the presence of saponins and flavonoids which had been shown to possess antioxidant and antimicrobial properties (Morebise and Fafunso, 1998;Hernández et al, 2000).…”
Section: Antibacterial Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…This observation agrees with previous reports by Oshodi et al(2004) that aqueous extracts of G. latifolium extracts show no activity against S. aureus. Results obtained in this work complement previous report on the usefulness of G. latifolium (Ugochukwu and Babady, 2002;Farombi, 2003;Morebise et al, 2002). Although compounds responsible for the observed bioactivity are unknown at this point, preliminary works and other reports show the presence of saponins and flavonoids which had been shown to possess antioxidant and antimicrobial properties (Morebise and Fafunso, 1998;Hernández et al, 2000).…”
Section: Antibacterial Activitysupporting
confidence: 87%
“…Reports by various authors showed that it contains essential oils, saponins and pregnanes among others (Schneider et al, 1993;Morebise and Fafunso, 1998;Morebise et al, 2002). , and Ogundipe et al(2003) reported that aqueous and ethanolic G. latifolium extracts had hypoglycemic, hypolipidemic and antioxidative properties while Morebise et al(2002) showed that it has anti-inflammatory properties. These reports are focused mainly on the medicinal properties of the plant with little attempts at investigating their potential nutritional and food processing/preservation values.…”
Section: Introductionmentioning
confidence: 99%
“…In Eastern Nigeria, the leaves are used to prepare soup for mothers that have recently put to bed, where it is believed to stimulate appetite, reduce post-partum contraction and enhance the return of the menstrual cycle. The traditional medicine practitioners in this region use Gongronema latifolium as a staple vegetable and spice in the management and treatment of a number of ailments amongst which is diabetes mellitus [10,11] and to support the pancreas regeneration [12]. In Sierra Leone, a decoction or cold infusion of the pounded stem is used for colic and intestinal symptoms usually associated with worms [13].…”
Section: Introductionmentioning
confidence: 99%
“…3,[18][19][20][21] Essential oils are important constituents of some higher plants and have been recognized to possess antimicrobial activities, 22 and phytochemicals are natural plant based chemicals that have been identified as active compounds in the prevention of degenerative diseases like diabetes mellitus and hypertension.…”
Section: Resultsmentioning
confidence: 99%